Dietrich Bonhoeffer and the ethical self : christology, ethics, and formation - Elliston, Clark J. (Clark James), 1980- (Fortress Press, 2016)
This volume argues that Bonhoeffer's early work, particularly his Christocentric anthropology, grounds his later expressed commitments to responsibility and faithfulness in a ""world come of age."" Ellison suggests, in fact, that a concern for otherness permeates all of Bonhoeffer's work: a Christian self-defined by its orientation towards otherness